Specyfika pracy tłumacza audiowizualnego na przykładzie wybranych komunikatów audiowizualnych - Borowczyk, Paulina (Investigationes Linguisticae, 2019)
The aim of the paper is to show the specificity and the complexity of audiovisual translation process. In the expository part of the paper I present the difference between translator of texts and audiovisual translator. I explain what elements take part in the construction of sense in audiovisual message and I show what kind of difficulties occur during the process of audiovisual translation (like technical restrictions). The Franco-German channel Arte is an example of a European company where the translation is used every day. The theoretical discussion is illustrated with the examples in which we can see how the translator use the informations from the screen to make polish subtitles shorter.